Genetic studies of pathogenicity in Botrytis cinerea (Botryotinia fuckeliana) : thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Science, Massey University - Weeds, Pauline; Weeds, Pauline (Massey University, 1997)
Botrytis cinerea is a common pleomorphic fungus causing 'grey mould' disease on a wide range of crops resulting in serious losses both pre- and post-harvest. Traditional control measures rely heavily on frequent fungicide applications. A greater understanding of the infection process and more information on the factors determining successful and unsuccessful host/pathogen interactions is important for the development of new control strategies. Although widely studied, relatively little is known about its genetics and the factors that determine its pathogenic ability. This study examines the genetics and pathogenicity of B. cinerea through mutation and selection. Two new genetic markers were developed based on resistance to the toxic analogues sodium selenate and potassium chlorate. These markers were then utilised in sexual crosses and competition studies in planta. Selenate resistant (SelR) mutants of Botrytis cinerea were selected by plating conidia or mycelial plugs onto minimal medium amended with selenate and taurine. Mutants could be divided into three classes based on growth in the presence of selenate or chromate and on improved growth in response to taurine in minimal media. Some mutants grew poorly on minimal media but were responsive to taurine, indicating they were defective in sulphate reduction. Strains showing the SelR phenotype may result from mutations in different genes; the genetic symbol Sel1 was allocated to one. Nitrate non-utilising (Nit) mutants, generated as spontaneous sectors on minimal media amended with chlorate, behaved as nit1 mutants in growth tests (putatively defective in nitrate reductase apoenzyme) and the genetic symbol nit1 was allocated to one of these mutants. When nit1 mutants were paired on medium with nitrate as sole nitrogen source, some pairings complemented, behaviour attributed to intragenic complementation. Selected crosses of SelR and nit1 mutants with wild type strains gave 1:1 segregation of both phenotypes and no evidence of linkage to either Mbc1 (benzimidazole resistance) or Daf1 (dicarboximide resistance) markers; loose linkage was confirmed between Mbc1 and Daf1. Both Sel1R and nit1 mutants were stable following subculture and retained pathogenicity in a French bean leaf assay. Complementation was demonstrated between a taurine responsive SelR mutant and a nit1 mutant selected from the same parent. Non-aggressive mutants were isolated from a single-ascospore strain of B. cinerea following mutagenic treatment (ultraviolet and 4-nitroquinoline-1-oxide) and screening on French bean leaves. Crosses with reference strains SAS56 or SAS405 revealed one u.v. mutant (Mp97) in which the non-aggressive phenotype segregated 1:1; indicating a single gene of major effect on pathogenicity to which the genotypic symbol Pat1 was allocated. No evidence of linkage was found between Pat1 and either Mbc1, Daf1, nit1 or Sel1. Further characterisation of this gene in studies involving Pat1 and wild-type strains revealed various host and temperature responses. Pat1 strains produced small, restricted lesions on French bean and soybean leaves and slowly spreading lesions on rose flowers. On tomato stems at 20 and 25°C the mutant was essentially non-pathogenic, although a reduced number of invasive infections were produced at 10 and 15°C. Pat1 strains grow/relatively normally, are indistinguishable from wild-type in gross morphology, and grow well on minimal medium indicating no unusual nutrient requirements, and it was concluded from comparison of physiological characteristics that the non-aggressive character is unlikely to be due to gross unfitness. No difference was found between Pat1 and wild-type strains in total polygalacturonase activity, and differences in polygalacturonase isozyme profiles were not correlated with the presence of the Pat1 gene. Pat1 was found to correlate with low acid production indicating a role for organic acid in pathogenesis of B. cinerea. Microscopic examination of 4-day-old lesions showed a distinctly stained ring of mesophyll cells surrounding lesions of Mp97 but not it's parent (A4), suggesting a difference in host response. Differences in phytoalexin induction in soybean were not found. It is possible that Pat1 strains may be deficient in the ability to tolerate or metabolise defence compounds. Two hypotheses are presented for further investigation. The first that Pat1 strains may have reduced toxicity due to low production of organic acids, and the second that these strains are non-aggressive due to a reduced ability to metabolise defence compounds. In competition experiments aggressive and non-aggressive strains were found to co-exist in the same lesion when inoculated at the same time but when challenge inoculations were delayed 6 hours or more the initial inoculation was found to dominate, suggesting non-aggressive strains may be useful as biocontrol agents.
Keywords: Grey mould disease; Botrytis cinerea growth